TH2.1: Who is a man? Understanding the local normative climate for transformative interventions in rural farming communities of Central Uganda - Businge, Martha; Mangheni, Margaret Najjingo; Mwiine, Amon A.; Shimali, Fred; Nakyewa, Brenda; Nanyonjo, G.; Angudubo, S.; Sanya, Losira N.; Asiimwe, E. (Makerere University, 2022)
Local gender normative climate refers to how norms in a community interact with men and women agency- their ability to make strategic life choices. Understanding the normative climate includes unpacking the community's expectations of what it means to be a man "masculinity norms". Such normative factors interact with and constrain opportunities for women's equitable participation in agriculture, yet most women empowerment literature focuses on individual women level factors. This ongoing study aims to determine masculinity norms that affect women's ability to make strategic choices within the Sasakawa Africa's Nutrition sensitive agricultural extension project intervention areas in Kiboga District, Central Uganda. The study utilized an interpretive qualitative case study with data collected from sex disagreggated focus group discussions with intervention beneficiaries. Findings indicate that the community expectation of who a man should be are along family formation and provisioning; dominance in household decision making and leadership; and community level participation. The normative structures also exempted men from participating in domestic chores and negative sanctions were experienced by men that did so. Gender roles espousing notions like "vegetable growing is a woman's domain" dissuaded men's engagement in this activity. Consequently, domestic chores on top of additional activities from vegetables growing under the project present an increased labor burden for women. Inability to make strategic life choices like attending training that would build their capacities in areas important for their development curtails their economic investments. This calls for development agents' deliberate efforts to engage both women and men to reframe norms and new behaviors that will foster gender equality and a harmoniously transformed community.